Portal pengetahuan zakat kajian kes: unit pungutan dan agihan zakat Majlis Agama Islam Negeri Johor - Mokhtar, Rashidah (2006)
Knowledge management is an increasingly important tools and valuable assets of competitive advantage for organizations. Among these KMS, knowledge portal present the potential to provide the organization with a rich and complex shared knowledge and also support knowledge management life cycle which are; create, storage, disseminate and use. The important aspects in knowledge portal (K-Portal) development are knowledge in zakat and effective K-Portal features. Target users for K-Portal Zakat are internal user (MAINJ Management) and external user (user who interested in knowing zakat). SECI Model and Aneja portal framework with knowledge life cycle by Mertins which are; create, storage, disseminate and use, integrated to identify K-Portal features that effective to give knowledge about zakat to people. The features that have been identify are taxonomy, personalization, collaboration, publishing, portal application, search and workflow. These features are chosen because there are suitable in zakat context. Knowledge based system development life cycle (KBSDLC) methodology is used in K-Portal development. While object oriented used in stakeholders analysis and identify the business processes. K-Portal Zakat has it own aims to create awareness among Muslim in doing their part in zakat and to realise the MAINJ mission, to increase Muslim social and economy